POTENSI OBJEK WISATA BUKIT SULIGI HILL DALAM MENDUKUNG KEGIATAN HIKING DI DESA ALIANTAN KABUPATEN ROKAN HULU - Ariani, Febri; Yulia, Nur Arini (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study aims to analyze the potential of Bukit Suligi Hill Tourism Object in supporting hiking activities in Aliantan Village, Rokan Hulu Regency. Hiking is a form of nature-based tourism that utilizes natural environmental conditions as its main attraction; therefore, it requires an area that remains natural, safe hiking trails, and adequate supporting facilities. This study employs a qualitative research method with data collection techniques including field observation, interviews, and documentation. The informants in this study consist of tourism site managers, local community members, and visitors to Bukit Suligi Hill.The results of the study indicate that Bukit Suligi Hill has considerable potential to be developed as a hiking tourism destination. The natural environment of the area remains relatively well preserved, although several parts have been utilized as community plantation areas. Bukit Suligi Hill offers hiking trails with varying levels of difficulty, making them suitable for both beginner and experienced hikers. In addition, the diversity of flora and fauna, including various types of natural vegetation and wildlife, serves as a distinctive attraction that enhances recreational and educational hiking experiences.However, the supporting facilities at Bukit Suligi Hill are still limited. The existing facilities include a parking area, toilets, resting areas, clean water facilities, and a camping area, while essential facilities such as an information center and gathering area are not yet available. Therefore, further development and improved management are required to maximize the potential of Bukit Suligi Hill as a safe, comfortable, and sustainable hiking tourism destination. Keywords: Hiking, Tourism Potential, Bukit Suligi Hill